The management in response to marine oil spill from ships in China: A systematic review. Issue 1 (15th July 2015) - Xiong, Shangao; Long, Hualou; Tang, Guoping; Wan, Jun; Li, Hongyuan
Graphical abstract: Highlights: Historical trends of marine oil spill incidents from ships in China. Status quo of marine ship-source oil spill management in China. Oil spill problem analyses and proposed mitigations. Management of marine oil spill pollution. Abstract: Historical trends about marine ship-source oil spill incidents from 1990 to 2010 in China were analyzed, and it provided an overview of the status quo of China's management in response to marine oil spill from ships. The Chinese government has issued a series of laws on marine environmental protection since 1982, and promulgated many regulations to prevent and tackle ship-source oil spill. At present, the oil spill emergency response system established in China has five levels: the national level, sea level, provincial level, port level, and ship level. China has demonstrated its ability to control and remove small-scale oil spill from ships in port area and near-shore coastal waters, and also paid attention to related research and development projects. Although China has made significant progress in managing shipping oil spill, challenges still exist, including strengthening oil spill emergency cooperation, enhancing China's response capability, and improving relevant research and development projects.